Enhancing Students’ Understanding of Hydrocarbon Nomenclature through Game-Based Learning : A Pre-Experimental Study - Rekfa Wika Amini; Arvidhea Safira Gunawan; Siti Shofa Assyifa'ul Qulbi Barid; Fauziyatul Iffah; Helda Wika Amini (Panthera : Jurnal Ilmiah Pendidikan Sains dan Terapan, 2026)
The study aims to examine improvements in students' understanding of hydrocarbon nomenclature following the implementation of the Wayground game-based learning in the General Chemistry I course. A quantitative approach with a pre-experimental one-group pretest–posttest design without a control group was employed. The participants consisted of 54 students from the Science Education Study Program who received instruction using the Wayground learning media. Data were collected using pretest and posttest instruments. The result revealed a large effect size (0.87) and a large N-gain (0.083), indicating a substantial improvement in students’ conceptual understanding. These findings indicate that Wayground game-based learning can enhance students’ understanding of hydrocarbon nomenclature and create a more engaging, interactive, and enjoyable learning environment.